The Recollections of Encolpius : the Satyrica of Petronius as Milesian Fiction. - Jensson, Gottskalk (Ancient narrative. Supplementum., 2004)
While nineteenth-century scholars debated whether the fragmentary Satyrica of Petronius should be regarded as a traditional or an original work in ancient literary history, twentieth-century Petronian scholarship tended to take for granted that the author was a unique innovator and his work a synthetic composition with respect to genre. The consequence of this was an excessive emphasis on authorial intention as well as a focus on parts of the text taken out of the larger context, which has increased the already severe state of fragmentation in which today's reader finds the Satyrica. The presen.